2019
DOI: 10.1088/1361-6382/ab4378
|View full text |Cite
|
Sign up to set email alerts
|

Weyl covariant theories of gravity in 3-dimensional Riemann–Cartan–Weyl space-times

Abstract: We discuss locally Weyl (scale) covariant generalisation of quadratic curvature gravity theory in three dimensions using Riemann-Cartan-Weyl space-times. We show that this procedure of Weyl gauging yields a consistent generalisation for a particular class of quadratic curvature gravity theories which includes the New Massive Gravity theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Note that the dual field strength, denoted by H, is a 1-form. Hence, we can choose C = κ H in the shift (22) where κ is a constant and (23) becomes…”
Section: Gauge Theory Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the dual field strength, denoted by H, is a 1-form. Hence, we can choose C = κ H in the shift (22) where κ is a constant and (23) becomes…”
Section: Gauge Theory Examplesmentioning
confidence: 99%
“…In [21] an alternative description of MMG based only on dreibein and spin connection is given where the Lorentz gauge symmetry is broken. Finally, in [22] it is shown that MMG is related with the break of the Weyl symmetry. It would be interesting to clarify connections between these different approaches.…”
mentioning
confidence: 97%
“…In this work, by using the exterior algebra notation, the matter coupling in MMG is studied by first considering that matter Lagrangian depends on the metric co-frame one-forms together with the matter fields and next concentrating on the case where the matter Lagrangian depends on the connection field as well. It should also be noted that within the same formalism, MMG has been worked out in the works [21][22][23][24] but without any consideration of the matter coupling. The first part of the study is in fact rephrasing of the work [13] by using the exterior algebra formalism.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, motivated by [19], we aim to investigate the pp-wave type solutions of MMG minimally coupled with Maxwell-Chern-Simons theory within the exterior algebra formalism. It should also be noted that using the same formalism, MMG has been studied in the works [20][21][22][23][24] where a detailed investigation of the matter-coupling in the exterior algebra formalism is performed in the work [24]. Now in the first part of the present study, we obtain the field equations by making variations of the matter-coupled MMG Lagrangian with respect to co-frames, connections, auxiliary one-form and Maxwell potential one-form fields.…”
Section: Introductionmentioning
confidence: 99%